Love of Variety and Gains from Trade - Christophe Gouel; Sébastien Jean (Center for Economic Studies and ifo Institute (CESifo), 2021)
This paper shows how gains from trade are conditioned by love of variety, defined as the extent to which an additional product variety generates benefits in either final or intermediate consumption. We develop a multi-country, multi-sector gravity trade model where love of variety is parameterized separately from product substitutability using a generalized CES demand function, and show analytically how gains from trade depend on love of variety through different channels that we identify and interpret. In this context, except for very specific parameterizations, gains from trade differ between a heterogeneous- and a homogeneous-firm model. Counterfactual simulations based on a calibrated version of this model show that, all other things being equal, the assessed gains from trade commonly vary by a proportion of one to three depending on the value of the love-of-variety elasticity, in a way that differs significantly across countries. Trade war simulations also point to the strong sensitivity of the assessed impacts. We conclude that love of variety is a key determinant of the gains from trade, an aspect that has so far been overlooked for the sake of convenience in the modeling framework and due to lack of empirical estimates.
Keywords: F11; F12; F13; 330; international trade; firm heterogeneity; gains from trade; gravity; love of variety